2018
DOI: 10.1186/s41983-018-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary monosymptomatic nocturnal enuresis: an etiological study

Abstract: Background: Nocturnal enuresis (NE) is a very common chronic pediatric problem with bad psychological consequences. Methods: Forty primary monosymptomatic nocturnal enuresis (MNE) children and 20 healthy controls were recruited in the study and subjected to history taking, neurological and urological examinations, and psychological assessment using the Arabic-translated and validated version of child behavior checklist, sleep architecture studying through onenight polysomnography (PSG), and vasopressin levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…There is a widespread issue with children called nocturnal enuresis that can lead to social stigma and emotional distress for the child and their family (13) . Multiple variables contribute to its complicated etiology.…”
Section: Discussionmentioning
confidence: 99%
“…There is a widespread issue with children called nocturnal enuresis that can lead to social stigma and emotional distress for the child and their family (13) . Multiple variables contribute to its complicated etiology.…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that in children with nocturnal enuresis, the ratio of REM sleep is lower and REM latency is longer than that of normal children. 40 However, according to Gu et al, there was no significant difference in sleep architecture between children with nocturnal enuresis and healthy controls. 41 In our study, REM sleep percentage was low in children with nocturnal enuresis compared with controls.…”
Section: Polysomnographic Findings In Nocturnal Enuresismentioning
confidence: 94%
“…A psychiatric evaluation was done using the Arabic translation of the Kiddie Schedule of Affective Disorders and Schizophrenia (K-SADS) [15]. The emotional and behavioral problems were assessed by using an Arabic validated form of the Child Behavior Checklist (CBCL) that was fulfilled by the guardians and scored by a computerized software system (Assessment Data Managerversion 9.1) [16].…”
Section: Methodsmentioning
confidence: 99%